'Co‐Production Is Caring': Young People's Reflections on Responsible and Dialogic Co‐Production in Youth Mental Health. - Mendes, Josimar Antônio de Alcântara; Mahamud, Ayan; Doherty, Sarah; Lucassen, Mathijs; Lockwood, Joanna; Townsend, Ellen; Hollis, Chris; Jirotka, Marina (Health Expectations, 2025)
Background: While co‐production is increasingly emphasised in youth mental health research, few studies have explored how young people themselves conceptualise and evaluate responsible and dialogic co‐production. Understanding young people's perspectives is essential to ensure that participation is meaningful and protective, rather than tokenistic or exploitative. This paper offers a retrospective reflection on a 3‐year UK youth mental health programme that embedded youth involvement and co‐production from the outset, at multiple levels (research participation, advisory and leadership). Objective: This study examines how young people involved in a UK youth mental health research articulate, from their own perspective, what counts as 'meaningful co‐production', centring its responsible, relational and dialogic dimensions. Design: A Qualitative Secondary Analysis was undertaken, applying Reflexive Thematic Analysis to explore patterns and meanings in participant accounts. Setting and Participants: Data comprised responses from five young people (three females and two males; M = 21 years, SD = 2.74) via an online open‐ended survey, and a focus group with eight young people (seven females and one male; M = 25.63 years, SD = 3.03). All participants had lived experience and were under 24 years old when they began their involvement in the youth mental health research programme on which this study is based. Results: Two central themes emerged: (1) 'We just want to be cared about': Co‐production is caring and (2) 'Please, show up as a person, not as a "researcher"': Co‐production as a dialogic process. Young people emphasised that meaningful co‐production, in youth mental health, is relational and affective (i.e., rooted in emotional care, mutual respect, flexibility and dialogue) and that the living experience of mental health is continuous and demands sensitivity. Discussion: These insights challenge procedural or ritualistic approaches to participation. Instead, they foreground care, reflexivity, power sharing and researcher presence as ethical prerequisites of co‐production. The results align with Responsible Research and Innovation (RRI) principles, highlighting the need to embed structural supports for emotional safety and relational engagement from the outset. Conclusions: Meaningful co‐production in youth mental health research requires embedding relational ethics into design and practice, ensuring young people are engaged as whole persons and partners. This model moves beyond procedural inclusion towards genuinely participatory research. Patient or Public Contribution: Young people with lived experience co‐designed the study materials, co‐facilitated the focus group, contributed to the interpretation and co‐authored the manuscript—ensuring that their perspectives are central to the study. Young people with lived experience of mental health were central to this study. Members of the programme's Young People's Advisory Group (YPAG) contributed to the design of the survey and focus group materials, ensuring they were youth‐friendly and relevant. Two YPAG members co‐facilitated the focus group alongside the first author, actively shaping the data collection process. Their insights and perspectives also informed the interpretation of the data, particularly in refining how themes captured relational and dialogic aspects of co‐production. Additionally, these two YPAG members are co‐authors of the manuscript, contributing to the conceptual framing, reflexivity and clarity of the results, ensuring that the work authentically reflects youth perspectives.